Analisis Pembiayaan Ijarah Perbankan Syariah - Yassir Arafat (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
At present there are many Islamic banks that have been established and developed in Indonesia, all Islamic banks compete with each other in making their products, as well as providing the best service to the community (customers) Many products have been operated by Islamic banks, among others: ijarah financing this product is shown to serve the community (customers). And one of the Islamic banking financing products opened to serve and facilitate the many Indonesian people who use ijarah financing. The problem formulation in this study is How is the ijaroh financing mechanism at KOSPPI, How is the suitability of ijaroh financing at KOSPPI with Islamic economic law? The data analysis method used in this research is descriptive qualitative method. In this study there are two things that will be analyzed, namely the Ijarah financing procedure and sharia accounting standards. Data collection used in this research is literature study, namely by reading or taking information from scientific journals, books and also utilizing the internet as a source of information. From the discussion above, the following conclusions can be drawn: that Islamic banking financing products based on lease contracts consist of pure leases and leases that end with the transfer of ownership rights or known as ijarah muntahiya bit tamlik. Ijarah vomia bit tamlik (IMBT) is basically a combination of leasing and buying and selling.